Hocus pocus : the game [games] - Marcellino, Ann (Ravensburger, 2020)
"The black flame candle has been lit. Now the Sanderson witches you must outwit; or with a wretched evil potion, a foul spell they'll set in motion. Stun the witches and ruin the brew before the sun can rise anew! Work together to protect Salem's children and stop the Sanderson sisters from completing their wicked potion before the sun rises!"--Container